Foraminiferal Analysis Related to Paleoceanographic Changes of Arafura Sea and Surrounding During Holocene - Luli Gustiantini; Swasty Aninda Piranti; Rina Zuraida; Sangmin Hyun; Duddy A.S. Ranawijaya; F.X. Harkinz Hendro Prabowo (Marine Geological Institute of Indonesia, 2018)
Arafura Sea is located between Papua and Australia as a part of Sahul Shelf. It is strongly influenced by ITF, ITCZ replacement, monsoon, and ENSO circulation that interplay with local mechanism. To understand the paleoceanographic parameter changes during Holocene, we conducted foraminiferal quantitative analysis from a 152 cm length sediment core (Aru–07), in every 10 cm interval. This sediment core was retrieved from 134o00’33.6” E, 5o55’51.59” S, by RV Geomarin 3 belongs to Marine Geological Institute. Geochronology of the sediment was reconstructed based on 2 AMS 14C age dates, analyzed on organic samples. We identified 129 species of benthic and 24 species of planktonic foraminifera that is dominated by planktonic specimens with average of 53.14%. Predominant species are Globigerina bulloides (16.16%), Globigerinoides ruber (11.18%), and Neogloboquadrina dutertrei (5.65%). Benthic type is dominated by genera Bolivina, Bulimina, and Uvigerina by 25.86% (average). This might suggest eutrophic condition associated with carbon-rich or low oxygen level (dysoxic) condition. Single linkage cluster analysis revealed 3 paleoenvironmental zones, are: Zone I: older than 3.9 kyr BP, characterized by depleted oxygen level and nutrient enrichment compared to that of younger zone. Zone II: 3.9 – 2 kyr BP, characterized by oxygen content enrichment and deeper thermocline layer, related to the sea level rise during more neutral or La Niña like condition. Zone III: younger than 2 kyr BP, represent shallower thermocline layer, higher productivity which might be related to upwelling, and dysoxic condition. Sea level might be declined that related to more El Niño like condition.Keywords: Paleoceanographic changes, upwelling, foraminiferal analysis, Arafura SeaLaut Arafura berlokasi di antara Papua dan Australia sebagai bagian dari Paparan Sahul. Kondisi iklim sangat dipengaruhi oleh ITF, perpindahan ITCZ, monsun, dan ENSO yang berinteraksi dengan mekanisme lokal. Untuk memahami perubahan parameter oseanografi selama Holosen, kami melakukan analisis kuantitatif mikrofauna foraminifera, yang dilakukan terhadap sebuah bor sedimen laut sepanjang 152 cm (Aru–07) pada interval setiap 10 cm. Bor sedimen bawah laut ini telah diambil pada posisi 134o00’33.6” BT, 5o55’51.59” LS, menggunakan kapal penelitian Geomarin 3, Pusat Penelitian Geologi Kelautan. Geokronologi sedimen berdasarkan 2 radiocarbon dating, dianalisis dari sampel organik pada sedimen. Teridentifikasi 129 spesies bentik dan 24 spesies plangtonik yang didominasi oleh plangtonik dengan persentase rata-rata 53.14%. Foraminifera Jenis–jenis yang dominan antara lain Globigerina bulloides (16.16%), Globigerinoides ruber (11.18%), dan Neogloboquadrina dutertrei (5.65%). Sedangkan jenis bentik didominasi oleh genus Bolivina, Bulimina, dan Uvigerina, dengan persentase rata–rata 25.86%. Hal tersebut kemungkinan menunjukkan kondisi eutropik yang berasosiasi dengan kondisi kaya karbon dan rendah level oksigen (disoxic). Analisis cluster single linkage menunjukkan tiga zona utama, yaitu: Zona I: lebih tua dari 3.9 kyr BP, dicirikan oleh relatif rendahnya kandungan oksigen dan lebih kaya kandungan nutrien. Zona II: 3.9 – 2 kyr BP, dicirikan oleh meningkatnya kandungan oksigen, dan mendalamnya lapisan termoklin, berkaitan dengan meningkatnya muka air laut ketika kondisi netral atau kondisi seperti La Niña. Zona III: lebih muda dari 2 kyr BP, merupakan zona dengan kondisi lapisan termoklin yang mendangkal, produktifitas meningkat yang kemungkinan berkaitan dengan upwelling, dan kondisi disoxic. Muka air laut kemungkinan turun, berasosiasi dengan kondisi seperti El Niño.Kata kunci: Perubahan paleoseanografi, upwelling, analisis foraminifera, Laut Arafura